0.08-0.02(x+2)=-0.03(2-x)

Simple and best practice solution for 0.08-0.02(x+2)=-0.03(2-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.08-0.02(x+2)=-0.03(2-x) equation:


Simplifying
0.08 + -0.02(x + 2) = -0.03(2 + -1x)

Reorder the terms:
0.08 + -0.02(2 + x) = -0.03(2 + -1x)
0.08 + (2 * -0.02 + x * -0.02) = -0.03(2 + -1x)
0.08 + (-0.04 + -0.02x) = -0.03(2 + -1x)

Combine like terms: 0.08 + -0.04 = 0.04
0.04 + -0.02x = -0.03(2 + -1x)
0.04 + -0.02x = (2 * -0.03 + -1x * -0.03)
0.04 + -0.02x = (-0.06 + 0.03x)

Solving
0.04 + -0.02x = -0.06 + 0.03x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.03x' to each side of the equation.
0.04 + -0.02x + -0.03x = -0.06 + 0.03x + -0.03x

Combine like terms: -0.02x + -0.03x = -0.05x
0.04 + -0.05x = -0.06 + 0.03x + -0.03x

Combine like terms: 0.03x + -0.03x = 0.00
0.04 + -0.05x = -0.06 + 0.00
0.04 + -0.05x = -0.06

Add '-0.04' to each side of the equation.
0.04 + -0.04 + -0.05x = -0.06 + -0.04

Combine like terms: 0.04 + -0.04 = 0.00
0.00 + -0.05x = -0.06 + -0.04
-0.05x = -0.06 + -0.04

Combine like terms: -0.06 + -0.04 = -0.1
-0.05x = -0.1

Divide each side by '-0.05'.
x = 2

Simplifying
x = 2

See similar equations:

| 8(-6c+7d)-2(5c-3d)= | | 7x-3=2(x-4) | | 1936=16t^2 | | 4(c+2)-2(c-3)=14c | | 23-7(x+3)*5x=10 | | 60/25 | | 1nx+1n(x+1)=3 | | -.50d+2=-.50(d+4) | | 23-7(x+3)*5=10 | | -2+4(6n-8)=-82 | | M/3-14=19 | | 53y+14y+7y+8y+22y+26y= | | 7y+6=29 | | (81^1/4)^4 | | 3x+14=180 | | -2(5c-3d)= | | 9(8+2+5v+3v)= | | X+6+6x=76 | | .03x-.15=.09 | | -6+88= | | 13x-42=0 | | 3x^2-2xs-8=0 | | M+0.36=9.75 | | 3n-4=29 | | F(x)=4x^2-16x+6 | | (X^2-14X-98)=0 | | 6+x+3x=-2 | | 6n+5=-151 | | 3y+y=2y-6 | | 2x+3x^2-22=0 | | -4/7x-4=12 | | 7a+4=102 |

Equations solver categories